Automobilität in Lateinamerika – eine historiographische Analyse - Peters, Mario (Anuario de Historia de América Latina, 2019)
Although car-ownership matters to many Latin Americans and cars are nearly omnipresent in daily life in Latin American societies, very little is known about important aspects of the social and cultural histories of automobility in Latin America. However, in the last ten years, several historians have begun to approach the meanings of automobility in Latin American countries. This trend is closely connected to recent developments and new approaches in the international research on mobility, the latter of which I discuss in the first part of this essay. To proceed, I analyze the state of the art on the history of automobility in Latin America, focusing on the following aspects: the emergence of early Latin American car cultures, car and traffic-related social conflicts, and road building. In the last part I ponder on the question of how future studies might advance the state of research on automobility and offer new perspectives on central themes in Latin American history.